(untitled) - Quigley, Carroll (Indianapolis, 1979)
Quigley defines a civilization as "a producing society with an instrument of expansion." A civilization's decline is not inevitable but occurs when its instrument of expansion is transformed into an institution—that is, when social arrangements that meet real social needs are transformed into social institutions serving their own purposes regardless of real social needs.
Keywords: Civilization,Nền văn minh; History,Lịch sử